Popular Hybrid Congenital Heart Procedures without Cardiopulmonary Bypass - Gupta, Aamisha; Amin, Zahid (Frontiers in Surgery, 2017)
As surgical and catheter interventions advance, patients with congenital heart disease are now offered alternative treatment options that cater to their individual needs. Furthermore, collaboration between interventional cardiologists and cardiac surgeons have led to the development of hybrid procedures, using the best techniques of each respective field to treat these complex cardiac entities from initial treatment in the pediatric patient, to repeat intervention in the adult. We present a review of the increased popularity and trend in hybrid procedures in congenital heart disease without the use of cardiopulmonary bypass.